Students’ Perception of Using WhatsApp during Online Learning - Ellsya Ninditha Maharani; Adhi Kusuma; Tutiek Murjiyah (Universitas Sarjanawiyata Tamansiswa, 2021)
The use of WhatsApp in learning is expected to motivate students in learning because WhatsApp has many features that helpful in learning. But students have different feelings, response, and perception towards the use of WhatsApp in learning. It is interesting to investigate the students’ perception, because everyone has different perceptions of the same object that been caused by many factors. The aim of this research is to find out and analyze the students’ feeling and response of WhatsApp that used by the teacher in learning. The researcher used quantitative research in this study. The researcher used questionnaire to collect the data. The questionnaire data in this research was analyze using SPSS version 24. The result of this research shows that the factors which influence the students’ perception of using WhatsApp in 12 Grade of SMKN 3 Tanjungpandan are the perceiver which is consisting of attitudes, motives, experience, and expectation. The target which is consisting of motion, sounds, size, background, and proximity. The situation which is consisting of time, work setting and social setting. The students’ attitudes of using WhatsApp in grade 12 of SMKN 3 Tanjungpandan shows the positive attitudes for the cognitive and behavioral components, but on the affective component shows negative result.